2014
DOI: 10.3389/fphy.2014.00064
|View full text |Cite
|
Sign up to set email alerts
|

Interparticle interactions between water molecules

Abstract: We determined many functional representations of interparticle interactions between water molecules, all of which reproduce the experimentally measured density-temperature relation at 1 bar with an accuracy better than obtained by previous models. Numerous similar descriptions of pair interactions will be discovered increasingly in the coming years, which will help us to understand why solid water has polymorphic structures and why liquid water has a large number of anomalies. We used a self-consistent Ornstei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…It is also found that the behavior of excess internal energy plays an essential role in the density anomaly and that the behavior is mainly determined by the value of the soft-repulsive potential, especially near the hardcore contact, depending on the attraction. Our results show that most of the ideas put forward up to now, such as the second critical point hypothesis, simple two-state model, liquid-liquid phase transition model, clathrate model, network model, hydrogen bonding, orientation-dependent potential, and so on, do not explain the direct causes of the density anomaly of liquid water, as we discussed in our previous article [41].…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…It is also found that the behavior of excess internal energy plays an essential role in the density anomaly and that the behavior is mainly determined by the value of the soft-repulsive potential, especially near the hardcore contact, depending on the attraction. Our results show that most of the ideas put forward up to now, such as the second critical point hypothesis, simple two-state model, liquid-liquid phase transition model, clathrate model, network model, hydrogen bonding, orientation-dependent potential, and so on, do not explain the direct causes of the density anomaly of liquid water, as we discussed in our previous article [41].…”
Section: Introductionmentioning
confidence: 74%
“…As a result, the liquid expands to become less dense as it is cooled further in the range of kT < kT 4 at a specified pressure. The behavior of the isothermal pressure-density curves shown in Figures 2, 3 is just what one can infer from the shape of the experimentally measured isobaric density-temperature curve of liquid water, which is exhibited in Figure 2 in Yasutomi [41] by open circles.…”
Section: Modelsmentioning
confidence: 99%
See 3 more Smart Citations